UJI HIPOGLIKEMIK EKSTRAK METANOL DAUN MAJAPAHIT (Crescentia Cujete (L.) TERHADAP KADAR GLUKOSA DARAH MENCIT JANTAN - Erwin -; Chaerul Saleh; Tika Purwitasari (JURNAL KIMIA MULAWARMAN, 2012)
Hypoglycemic test of methanol extract of Crescentia cujete (L.) at dose 25 mg/kg, 50 mg/kg and 75 mg/kg given to male laboratory mice orally with glucose tolerance test method has been done. Measurement of blood glucose was carried out every 30, 60, 90, 120, 150 and 180 minutes with glucometer. Result of this research concluded that addition of methanol extract of dose 25 mg/kg gave strongest hypoglycemic effect (25.20%), followed at dose 50 mg/kg (18.00%) and at close 75 mg/kg (10.01%) at confidence limit 0.05. Phytochemical test of methanol extract of Crescentia cujete (L.) leaves shown presence of alkaloids, terpenoids, phenolic and saponin compounds.Keywords: Hypoglycemic, Crescentia cujete (L.), phyatochemical